Screening Status Gizi Dan Kelas Literasi Gizi Anak Sekolah Di SD X Kota Makassar - Mukty, Ma'rifat; Jusriani, Rini; Kusuma, Nina; Ilyas, Asmiana; Syafri, Muhammad (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2025)
Abstract Nutritional status is a critical indicator in assessing children's health, growth, and development, as well as in preventing future diseases. The Body Mass Index-for-Age (BMI-for-age) is commonly used to measure children's nutritional status, encompassing categories such as undernutrition, overnutrition, and obesity. This study aims to analyze the nutritional status of primary school children based on BMI-for-age and evaluate the relationship between their nutritional knowledge and nutritional status. The study involved 58 children, with data collected through anthropometric measurements and a nutrition knowledge questionnaire. Results indicated that 65.5% of the children had a normal nutritional status, while 34.5% had an abnormal nutritional status, comprising 13 undernourished children, 5 overnourished, and 2 obese. Before the post-test, 90% of the children demonstrated good nutritional knowledge, which increased to 100% post-test. However, the high level of nutritional knowledge did not always correlate with an ideal nutritional status, highlighting the need for a more holistic approach to nutrition education and regular nutritional monitoring. These findings emphasize the importance of further interventions to comprehensively improve children's nutritional status. Keywords: Nutritional Status, BMI-for-age, School Children, Nutrition Education